Ex-post Environmental Impact Assessment: Lessons from four CGIAR case studies - CGIAR Independent Science and Partnership Council (CGIAR Independent Science and Partnership Council, 2012)
This brief is based on the paper by Jeff Bennett (2011) Advancing ex-post impact assessment of environmental impacts of CGIAR research: conceptual issues, applications and the way forward. In: CGIAR Independent Science and Partnership Council (2011). Measuring the Environmental Impacts of Agricultural Research: Theory and Applications to CGIAR Research.